Clarification of Taxonomic Status within the Pseudomonas syringae Species Group Based on a Phylogenomic Analysis - Gomila, Margarita; Busquets, Antonio; Mulet, Magdalena; García-Valdés, Elena; Lalucat, Jorge (Frontiers in Microbiology, 2017)
The Pseudomonas syringae phylogenetic group comprises 15 recognized bacterial species and more than 60 pathovars. The classification and identification of strains is relevant for practical reasons but also for understanding the epidemiology and ecology of this group of plant pathogenic bacteria. Genome-based taxonomic analyses have been introduced recently to clarify the taxonomy of the whole genus. A set of 139 draft and complete genome sequences of strains belonging to all species of the P. syringae group available in public databases were analyzed, together with the genomes of closely related species used as outgroups. Comparative genomics based on the genome sequences of the species type strains in the group allowed the delineation of phylogenomic species and demonstrated that a high proportion of strains included in the study are misclassified. Furthermore, representatives of at least 7 putative novel species were detected. It was also confirmed that P. ficuserectae, P. meliae and P. savastanoi are later synonyms of P. amygdali and that “P. coronafaciens” should be revived as a nomenspecies.